Cancer incidence in the Western Australian mining industry (1996–2013) - Sodhi-Berry, N.; Reid, Alison; Fritschi, L.; Musk, A.; Vermeulen, R.; de Klerk, N.; Peters, S. (Elsevier Inc., 2017)
Background: Miners are frequently exposed to established and potential carcinogens. We aimed to assess cancer incidence in miners relative to the general population and identify high-risk subgroups. Methods: Incident cancers in Western Australian miners (n = 153,922; 86% male) during 1996–2013 were identified. Indirectly standardised incidence ratios (SIRs) were calculated and mixed-effects Poisson models were used to calculate Incidence Rate Ratios (IRRs) to identify high-risk within-cohort subgroups. Results: Compared with the general population, the overall cancer incidence in miners (n = 4194 cases) was lower for both females (SIR:0.83, 95%CI:0.74–0.92) and males (SIR:0.96, 95%CI:0.93–0.99). Overall, cancer incidence did not differ by employment duration or employment commencement time. Ever-underground work was associated with lung cancer (IRR:1.81, 95%CI:1.11–2.93). Relative to multi-ore miners, IRRs for specific cancers were significantly different when exclusively mining: iron (prostate:0.73, 95%CI:0.56–0.94); gold (lung:1.77, 95%CI:1.04–3.01 and colorectum:1.70, 95%CI:1.16–2.51); and other metals (urinary tract:1.85, 95%CI:1.03–3.31 and leukaemia:0.36, 95%CI:0.14–0.96). Conclusion: Working underground emerged as a significant determinant of lung cancer risk in our contemporary mining cohort. Increased risks of lung, prostate, colorectal and urinary tract cancers and leukaemia were identified in miners of specific ores. These findings underline the importance of continued surveillance of the health and exposures of this relatively young cohort of miners.